Program Aplikasi Persediaan Barang Dagang Berbasis Web Terintergrasi pada UD. Ismail Dengan Metode FIFO - Nadia Puteri Utami; Heru Kartika Candra; Kukuh Yustisio (Journal Of Business, Finance, and Economics (JBFE), 2022)
This study discusses the application of an inventory accounting information system at UD Ismail. The purpose of this research is to find out a good and correct inventory accounting information system, and to produce a Web-Based Merchandise Inventory Application Program. Theoretical framework is to analyze the Inventory Accounting Information System by analyzing the required information. Namely by analyzing the information needed by management, related functions, documents and accounting records used, document flowcharts (flowchart). And the program that was developed the first step was to design the relations between tables. Designing interfaces. And output design. From this research, it was found some facts where inventory recording at UD Ismail still uses a semi-manual system. The author suggests using a web-based inventory application program in order to facilitate and assist UD Ismail in recording and making inventory reports.